Discourse on Visuality in the Digital Age - Grażyna Penkowska; Małgorzata Karczmarzyk (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: The widespread availability of mobile technologies has resulted in changes in interpersonal communication in favor of a significant increase in visual communication. The growing role of the visual representation in communication processes gives rise to, e.g. questions: about the assessment of its effectiveness in comparison with the verbal message, about the chances of intercultural understanding beyond the language, as well as about the effects of language marginalization for the development of culture, in particular language culture. The text below is a voice in the discussion on the contemporary meaning of visuality and raises issues that are important especially for educators. Research Aim: The subject of consideration is to indicate various contexts related to visuality, with particular emphasis on the understanding of graphic messages in education. The aim of the undertaken research was to check the thesis whether a work of painterly art can be a plane of common meanings. In a broader perspective, we ask whether verbal and visual communication can be treated alternatively. Method: The methods used for the research are: semiotic analysis of the "open work" and discourse analysis. Results: In addition to individual semiotic analyzes of student interviews, tables of differences and similarities were developed. The semantic and discursive analyzes show the similarities and differences in the perception of images by the surveyed female students, as well as the discourses that arose in the course of visual communication through images. Conclusion: Based on the individual and semantic analysis of student interviews, it can be concluded that both the signs in the images and the meanings created by the respondents are a kind of communication carriers. Visual discourses of images become a platform on the basis of which communication and understanding between the subjects is possible.